Development of the ANCOR Dashboard - Cain, Brian (Kansas State University, 2014)
In this paper I present ANCOR Dashboard, a front end web framework that interfaces with ANCOR. ANCOR Dashboard aims to provide ANCORs users with an easy to use front end interface for accomplishing various use-cases against the ANCOR framework. ANCOR Dashboard was developed mainly in AngularJS, a lightweight JavaScript framework. This dashboard is able to accomplish everything that the ANCOR Command Line Interface, or ANCOR-CLI, is able to do. This framework also needed to provide some information about the state of the system through various data gathered from ANCOR in a human readable format. Not only should it be able to inform the user about the state of ANCOR but it needs to be able to perform operations against ANCOR just like the command line interface can do.This report documents the design and implementation of ANCOR Dashboard. It will detail the necessary background of the project, and overview of the framework, and discus- sion of implementation and component breakdown. I will also provide an evaluation of the dashboard and a discussion about future work with ANCOR Dashboard.
Keywords: Computer science; Computer Science (0984)